2007
DOI: 10.1002/tre.37
|View full text |Cite
|
Sign up to set email alerts
|

Penile fracture: diagnosis and management

Abstract: Penile fracture is an uncommon urological emergency that can have significant complications. Patients usually present to the accident and emergency department, but may seek advice from GPs. Immediate surgical repair is the treatment of choice, with fewer complications, shorter hospital stays, better outcome and increased patient satisfaction compared with conservative therapy. Copyright © 2007 Wiley Interface Ltd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 0 publications
0
30
0
1
Order By: Relevance
“…Quick and accurate decision making is the key to the safe management and successful outcome in patients with penile fracture [13,14]. To identify and interpret grading system was done with ease by USG.…”
Section: Discussionmentioning
confidence: 99%
“…Quick and accurate decision making is the key to the safe management and successful outcome in patients with penile fracture [13,14]. To identify and interpret grading system was done with ease by USG.…”
Section: Discussionmentioning
confidence: 99%
“…The patients will often report hearing a cracking noise during sexual activity (albuginean rupture) followed by immediate pain, detumescence, and a slowly expanding penile hematoma often described as an "eggplant deformity" [8,9]. If Buck's fascia is involved, the ecchymosis can progress along the fascial planes and compromise the scrotum and the perineum [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is recommended that patients refrain from sexual activity six to eight weeks to prevent refracture, some authors have found no recurrence in patients who had intercourse in the two subsequent weeks [9]. Early surgery is not only the treatment of choice for managing penile fractures but also prevents the development of posttraumatic anatomical alterations.…”
Section: Penile Fractures Complicationsmentioning
confidence: 99%
“…The high precision of the method allows differentiating vascular sinusoids of the cavernous body from the tunica albuginea, achieving high diagnostic accuracy 5,6 . MR imaging is the diagnostic modality of choice because it precisely demonstrates the presence, location, and extent of the tunical tear, which manifests as discontinuity of the tunica albuginea 6,7,8 . MR imaging also depicts associated injuries to adjacent structures (i.e., corpus spongiosum, urethra) 6 .…”
Section: Discussionmentioning
confidence: 99%